f(1)+g(1)=-7+1=-6
and f(3)-g(3)=-13-9=-22
2007-01-09 14:09:40
·
answer #1
·
answered by Zidane 3
·
0⤊
0⤋
(f+g)(1)=(-3x-4) + (x^2)
=(-7) + 1
= -6
(f-g)(3)=(-3x-4) - (x^2)
=(-13) - 9
= -22
2007-01-09 14:15:16
·
answer #2
·
answered by chrisjptine 1
·
0⤊
0⤋
First you get (f+g)(x) and (f-g)(x)
(f + g)(x)= f+g = ( -3x-4) +( x^2 ) =x^2 -3x-4
(f - g)(x)= f-g = ( -3x-4) - ( x^2 ) = -x^2 -3x-4
So (f + g)(1) = (1)^2 -3(1)-4= -6
And (f - g)(1) = -(1)^2 -3(1)-4= -8
2007-01-09 14:12:52
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
(f+g) (1)=f(1)+g(1)=(-6)
(f-g) (3)=f(3)-g(3)= -13-9= (-22)
2007-01-09 14:12:34
·
answer #4
·
answered by zoomalways 2
·
0⤊
0⤋
f(x) = -3x - 4
g(x) = x^2
(f + g)(1) =
f(1) + g(1) =
(-3(1) - 4) + (1^2) =
(-3 - 4) + 1 =
-7 + 1 =
-6
ANS : -6
---------------------------------------------
(f - g)(3) =
f(3) - g(3) =
(-3(3) - 4) - (3^2) =
(-9 - 4) - (9) =
-13 - 9 =
-22
ANS : -22
2007-01-09 14:46:51
·
answer #5
·
answered by Sherman81 6
·
0⤊
0⤋
i can't answer your question, but i saw it as i was passing by...
i just wanted to wish you luck! i'm about to start algebra 2 in college and i'm scared to death!
2007-01-09 14:13:01
·
answer #6
·
answered by daddielovesmuffin 1
·
0⤊
0⤋